2004
DOI: 10.1101/gad.1187704
|View full text |Cite
|
Sign up to set email alerts
|

Natural genetic variation in Arabidopsis identifies BREVIS RADIX, a novel regulator of cell proliferation and elongation in the root

Abstract: Mutant analysis has been tremendously successful in deciphering the genetics of plant development. However, less is known about the molecular basis of morphological variation within species, which is caused by naturally occurring alleles. In this study, we succeeded in isolating a novel regulator of root growth by exploiting natural genetic variation in the model plant Arabidopsis. Quantitative trait locus analysis of a cross between isogenized accessions revealed that a single locus is responsible for ∼80% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
249
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(263 citation statements)
references
References 46 publications
8
249
0
6
Order By: Relevance
“…Most of these SNPs mapped to two genomic regions in chromosomes III and IV (Fig. 2C), partially overlapping regions with previously identified root morphology quantitative trait loci (QTL) (4)(5)(6)(15)(16)(17)(18). We assumed a 5-kb window before the first and after the last significant SNPs, given that linkage disequilibrium decays more than 50% in Arabidopsis in that range (19).…”
Section: Identification Of Candidate Genes Underlying Natural Variatimentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these SNPs mapped to two genomic regions in chromosomes III and IV (Fig. 2C), partially overlapping regions with previously identified root morphology quantitative trait loci (QTL) (4)(5)(6)(15)(16)(17)(18). We assumed a 5-kb window before the first and after the last significant SNPs, given that linkage disequilibrium decays more than 50% in Arabidopsis in that range (19).…”
Section: Identification Of Candidate Genes Underlying Natural Variatimentioning
confidence: 99%
“…We took a unique approach to integrating results from these two perspectives to uncover the molecular basis underlying individual plasticity and variation among natural variants. We focused on the root architectural system because it shows a high degree of plasticity under diverse environmental conditions (4)(5)(6)(7)(8)(9). We used a quantitative phenotyping model to capture and integrate plastic changes in root system architecture in response to a range of experimental treatments within the laboratory reference accession Columbia-0 (Col-0).…”
Section: Integration Of Responses Within and Across Arabidopsis Naturmentioning
confidence: 99%
“…Natural variation within Arabidopsis has been the basis for many studies on plant morphology, physiology, and development as well as stress response (Alonso-Blanco et al, 2009;Weigel, 2012). Natural variation of root traits such as primary root length (Mouchel et al, 2004;Loudet et al, 2005;Sergeeva et al, 2006), LR length (Loudet et al, 2005), and total root size (Fitz Gerald et al, 2006) have pinpointed genomic regions underlying the phenotypic variation via mapping of quantitative trait loci (QTLs) as a first step toward the identification of novel regulatory genes (Mouchel et al, 2004). This strategy has also been applied to environmental responses, such as growth responses to phosphate starvation (Reymond et al, 2006;Svistoonoff et al, 2007).…”
mentioning
confidence: 99%
“…The BRX gene was identified by quantitative trait loci (QTL) analysis and shown to be responsible for about 80% of the variation of the PR length in an RIL population derived from crossing an accession with a long PR with one with a very short PR. BRX controls the cell proliferation and elongation (Mouchel et al, 2004). Subsequent analysis showed that BRX mediates the interaction between brassinosteroids and auxin pathways, which is required for root growth (Mouchel et al, 2006).…”
Section: Using Natural Variation To Identify Regulators Of Root Growtmentioning
confidence: 99%
“…However, such efforts were largely restricted to processes that could be observed in above-ground tissues, and for almost 10 years, allelic variation of only one gene, BRE-VIS RADIX (BRX), was known to be specifically involved in natural variation of root development (Mouchel et al, 2004). The BRX gene was identified by quantitative trait loci (QTL) analysis and shown to be responsible for about 80% of the variation of the PR length in an RIL population derived from crossing an accession with a long PR with one with a very short PR.…”
Section: Using Natural Variation To Identify Regulators Of Root Growtmentioning
confidence: 99%